Developing and testing a theory of change for Boy Scouts of America. Issue 3 (3rd July 2022) - Urban, Jennifer Brown; Linver, Miriam R.; Moroney, Deborah; Nichols, Trent; Hargraves, Monica; Roberts, E. Danielle; Quinn, Johanna; Brown, Megan; Gama, Lauren; Doubledee, Rachael; Cox, Milira
Abstract: Positive youth development programs such as those offered by Boy Scouts of America (BSA) provide sources of support and opportunities for leadership and character development. Programmatic experts from BSA collaborated with researchers to develop a visual theory of change (pathway model) for youth development in Scouts BSA and for adult volunteer leader development. The pathway model was then validated through focus groups with Scouts BSA youth and adult leaders across the country. Practice mapping was employed to assess the consistency of pathway models with core adult training curricula. The models were aligned with research literature through evidence mapping. The theory of change embedded in the Scouts BSA program was aligned with the Big Three features of positive youth development programs.